Individual patient data meta-analysis of beta-blockers in heart failure: rationale and design. - Kotecha, D; Manzano, L; Altman, D; Krum, H; Erdem, G; Williams, N; Flather, MD (2013)
UNLABELLED: The Beta-Blockers in Heart Failure Collaborative Group (BB-HF) was formed to obtain and analyze individual patient data from the major randomized controlled trials of beta-blockers in heart failure. Even though beta-blockers are an established treatment for heart failure, uptake is still sub-optimal. Further, the balance of efficacy and safety remains uncertain for common groups including older persons, women, those with impaired renal function and diabetes. Our aim is to provide clinicians with a thorough and definitive evidence-based assessment of these agents. We have identified 11 large randomized trials of beta-blockers versus placebo in heart failure and plan to meta-analyze the data on an individual patient level. In total, these trials have enrolled 18,630 patients. Uniquely, the BB-HF group has secured access to the individual data for all of these trials, with the participation of key investigators and pharmaceutical companies.Our principal objectives include deriving an overall estimate of efficacy for all-cause mortality and cardiovascular hospitalization. Importantly, we propose a statistically-robust sub-group assessment according to age, gender, diabetes and other key factors; analyses which are only achievable using an individual patient data meta-analysis. Further, we aim to provide an assessment of economic benefit and develop a risk model for the prognosis of patients with chronic heart failure.This paper outlines inclusion criteria, search strategies, outcome measures and planned statistical analyses. TRIAL REGISTRATION: CLINICAL TRIAL REGISTRATION INFORMATION: http://clinicaltrials.gov/ct2/show/NCT00832442.